2009
DOI: 10.1111/j.1472-8206.2009.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of seizures and biochemical parameters of oxidative stress in experimentally induced inflammatory rat models

Abstract: The role of oxidative stress in the pathogenesis of various conditions including epilepsy, inflammatory bowel disease and rheumatoid arthritis is evolving. The aim of this study was to find out the correlation between various inflammatory models with seizures and antioxidant parameters. Fifty-four male rats were divided into three groups of colitis, adjuvant arthritis and cotton wool granuloma (CWG). Each group had three subgroups of control, model and treatment. Thalidomide was used as treatment in colitis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Oxidative stress products, primarily generated by infiltrating neutrophils, are another important aspect of the inflammatory process . It has been shown that cytokines, including TNF‐α and IL‐1β, can induce the production of H 2 O 2 and superoxide, leading to nuclear factor κB (NFκB) activation, which upregulates cytokine production .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress products, primarily generated by infiltrating neutrophils, are another important aspect of the inflammatory process . It has been shown that cytokines, including TNF‐α and IL‐1β, can induce the production of H 2 O 2 and superoxide, leading to nuclear factor κB (NFκB) activation, which upregulates cytokine production .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, oxidative stress has been identified as the main mechanism of seizure activity. Inflammation also plays an essential role in epilepsy development [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Em monócitos de pacientes AR e sadios tratados com TNF-α ou TNF-α+TAL, a TAL inibiu a translocação citoplasmática da proteína intracelular de alta mobilidade de grupo caixa-1 (HMGB1) causada peloTNF-α (ZUO et al, 2008). Entre os estudos avaliando a TAL no tratamento da artrite experimental em ratos(RAO et al, 2010;ALEXANDRE-MOREIRA et al, 2005;OLIVER et al, 1999;OLIVER et al, 1998) e camundongos (HAUSCHILD et al, 1997KRÖGER et al, 1996), apenas um apontou efeitos negativos(OLIVER et al, 1999). Sobretudo, alguns dos ensaios clínicos já feitos com essa droga no tratamento da AR indicaram efeitos benéficos(GUTIÉRREZ-RODRÍGUEZ et al, 1989;…”
unclassified